The Impact of Developmental Leadership on Adaptive Performance- Analytical Research General Directorates of Education in Baghdad province - Hussein Sha’alan, Uday; Kadhim Saaed, Hadeel (Journal of Economics and Administrative Sciences, 2023)
The research aims to reveal the impact of developmental leadership in its dimensions (ideal model, interest in employees, inspiration and motivation) as an independent variable in achieving adaptive performance in its dimensions (Creative problem solving, learning and motivation, Training efforts, adaptability, work stress management, dealing with crises and emergencies) as a dependent variable, and the research aims to enhance the quality of developmental leadership in the research sample through this leadership style, which is a modern style and is still under research and study with a focus on the benefit of adaptive performance From a psychological and organizational research sample consisting of (106) respondents from the middle administrative leaders in the general directorates of education in Baghdad governorate, adopting the questionnaire as a main tool in data collection, and using a number of statistical methods, including (standard deviation, Soble test, and Pearson correlation coefficient). There is a positive and direct significant relationship between developmental leadership and adaptive performance in general, but at the level of dimensions, it was strong with the dimension of (learning and training efforts) and from medium to strong with (the dimension of personal adaptation and management of work pressures and emergencies.Paper type: Research paper.